Sprint start performance: the potential influence of triceps surae electromechanical delay - Crotty, E. D.; Hayes, K.; Harrison, A. J. (Sports Biomechanics, 2022)
In the sprint start, a defined sequence of distinct response delays occurs before the athlete produces a movement response. Excitation of lower limb muscles occurs prior to force production against the blocks, culminating in a movement response. The time delay between muscle excitation and movement, electromechanical delay (EMD), is considered to influence sprint start response time (SSRT). This study examined the delay in sprint start performance from EMD of the triceps surae muscle and examined whether certain sprinters gain an advantage in SSRT. Nineteen experienced sprinters performed sprint starts from blocks, with SSRT measured by an International Association of Athletics Federations (IAAF)-approved starting block system. EMD times were detected during a heel-lift experiment. Using revised SSRT limits, based on concerns over the validity of the IAAF 100 ms false start limit, EMD produced a significant moderate correlation with SSRT (r = 0.572, p = 0.011). Regression analysis determined that together, EMD and signal processing time (the delay between the auditory signal and muscle excitation) accounted for 37% of the variance in SSRT. Initial results suggest EMD is part of the response time process and that certain athletes may gain a performance advantage due to reduced EMD.